Introducing design for selective laser melting in aerospace industry. Issue 4 (10th April 2020) - Stolt, Roland; Elgh, Fredrik
Abstract: The selective laser melting (SLM) process has created new possibilities for the manufacture of new lightweight jet engine components with lattice structures replacing solid sections. Hopes are to reduce the density of the component and thereby saving weight. To introduce the new manufacturing process, the components need to be redesigned and verified to comply with an array of requirements concerning, for example, strength, aerodynamics, and manufacturing. To find out how a capability of designing and evaluating components for the SLM process can be built into an organization, an interview investigation has been conducted at an aerospace company finding the state of practice in technology and product development. The impact of introducing SLM is thereafter estimated. The result is that introducing a novel manufacturing process will primarily influence the methods used to predict product lifecycle performance. An important finding is that it is currently difficult to include a topology optimization step in the multiobjective design evaluation environment used at the company due to which the complexity would increase significantly. Graphical Abstract: